Modeling and simulation of maintenance operations at Kuwait public transport company - SAVSAR, MEHMET (Kuwait Journal of Science, 2013)
In this study, a simulation model is developed to analyze and improve maintenance operations of a bus fleet at Kuwait Public Transport Company (KPTC). Bus fleet maintenance has been one of the major problems at KPTC. The company operates about 600 buses daily on 40 different routes for public transportation in Kuwait. Frequently these buses fail and need corrective maintenance in addition to regular preventive maintenance activities. The company has two maintenance locations, which handle 349 and 248 buses each. In this study, the facility for 349 buses is analyzed in detail and the effects of several operation strategies on system performance are evaluated by a simulation model. The simulation results are incorporated into a cost model in order to evaluate each strategy. The results show that significant savings can be achieved by using an appropriate operation policy.